2007
DOI: 10.1007/s00264-007-0467-x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative laxity in osteoarthritis patients undergoing total knee arthroplasty

Abstract: A preoperative quantitative evaluation of soft tissues is helpful for planning total knee arthroplasty, in addition to the conventional clinical examinations involved in moving the knee manually. We evaluated preoperative coronal laxity with osteoarthritis in patients undergoing total knee arthroplasty by applying a force of 150 N with an arthrometer. We examined a consecutive series of 120 knees in 102 patients. The median laxity was 0°in abduction and 8°in adduction. The femorotibial angle on non-weight-bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The reference lists of the final set of articles were checked to identify additional manuscripts to include in the review, but every article of interest had already been included in the initial search. Of the 40 selected studies, 4 were prospective trials, [18][19][20][21] 16 were cohort-control designs, 11,14,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] and the remaining 20 were cross-sectional studies. 13,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Laxity was a primary variable of interest in 32 of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference lists of the final set of articles were checked to identify additional manuscripts to include in the review, but every article of interest had already been included in the initial search. Of the 40 selected studies, 4 were prospective trials, [18][19][20][21] 16 were cohort-control designs, 11,14,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] and the remaining 20 were cross-sectional studies. 13,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Laxity was a primary variable of interest in 32 of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, 11 found a significant increase in some measure of laxity in the OA group compared with controls, 11,23,25-31,33,34 4 found no difference, 14,22,32,35 and 2 did not report any statistical comparisons between groups as this was not the focus of those manuscripts. 20,24 In the studies which found increased laxity, four reported increased total varus-valgus laxity, 11,23,25,31 six had increased medial, but not lateral, compartment laxity in subjects with medial knee OA, [26][27][28][29][30]34 and one found increased total varus-valgus laxity after stair climbing but not before activity. 33 Quantified varus-valgus angular laxity and joint space laxity results from these 17 studies are shown in ►Table 1 and ►Table 2, respectively.…”
Section: Osteoarthritis Versus Controlsmentioning
confidence: 97%
“…However, these measurements were performed before surgery or bone resection [1,3,9,16,20]. Therefore, surgeons try to correct intraoperative imbalance by releasing the medial soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Stress radiographs under varus and valgus conditions enable a better determination of the stability of the knee joint [12], but involve additional radiation exposure and greater costs and are therefore reserved for special questions [13]. In contrast to this, the pre-operative long standing X-ray is standard in most hospitals, as it is necessary for planning the tibial and femoral resection planes in relation to the mechanical axis [14][15][16].…”
Section: Introductionmentioning
confidence: 99%